Shock-probe Defensive Burying Test to Measure Active versus Passive Coping Style in Response to an Aversive Stimulus in Rats - Fucich, Elizabeth A. (Bio Protoc, 2018)
Maladaptive avoidance behaviors are seen in many stress-related psychiatric illnesses. Patients with these illnesses favor passive, avoidant coping strategies rather than adaptive, active coping strategies. Preclinically, coping strategy can be measured in rats using the shock-probe defensive burying test, wherein rats receive a shock from an electrified probe inserted into a test cage that mimics their home cage environment, and behavioral output (immobility or burying) is recorded for 15 min following the shock. Immobility in response to the perceived threat of the shock-probe, associated with elevated stress hormone levels, is regarded as a passive, maladaptive coping strategy. In opposition, burying the probe is associated with lower stress hormone levels and is considered an active, adaptive coping style. In rats, chronic stress induces a shift from active to passive coping in this test (i.e., proportionally less burying and more immobility), modeling the avoidant symptoms presented across many stress-related psychiatric illnesses. The stress-induced shifts in coping style and overall behavioral reactivity to the shock-probe provide a unique and well-validated measure of not only an anxiety-like behavioral response but also coping strategy selection in rat models of psychiatric illness.